Meroe, Sudan. Fieldwork at the Royal Cemeteries of Meroe – A Progress report of the Qatari Mission for the Pyramids of Sudan. The years 2017 and 2018 - Wolf, Pawel; Riedel, Alexandra (e-Forschungsberichte des DAI, 2019)
In 2017 and 2018 significant milestones in several key aspects of the mission’s program have been reached. After the successful completion of the archaeological documentation at Queen Khennuwa’s tomb Beg. S. 503 and the iconographic and epigraphic studies of its burial chamber decoration, the post-excavation analysis of this important royal tomb started. The architectural and iconographic documentation of the Begrawiya North and South cemetery pyramids and their offering chapels has been completed in the field, and the collection, inventory, and preliminary documentation of more than 1000 ornamented blocks that were found out of their original context have been achieved. An important step was reached by the preparation of a general conservation and preservation strategy for the pyramids and their chapels. Its implementation meanwhile started at both cemeteries. Furthermore, the development of a sustainable tourism plan for Meroe and the ‘Island of Meroe’ was finalised and the implementation of necessary infrastructure commenced by the implementation of an improved site entrance, a visitor centre and fencing of site boundaries at various places.